Pemaknaan Penonton Perempuan Terhadap Beauty Influencer Laki-Laki di TikTok - Nur Rizky Dewi Angelita; Johny Alfian Khusyairi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
This study aims to discuss the female audience's reception of the existence of male beauty influencers in the TikTok application. The aspect of beauty in Indonesia has always been synonymous with women, but in its development, male beauty influencers have emerged who have similar goals, namely educating women and men regarding aspects of beauty. The research used qualitative methods with in-depth interviews and observation instruments. The six informants consisted of women who often watch beauty content and are active in the TikTok application. Data analysis used Stuart Hall's reception analysis theory. The results of the study show that the majority of informants are in the negotiated position category, which is accepting and agreeing with the information conveyed by male beauty influencers, but there are some things that are still being considered.